2013
DOI: 10.1007/s12160-013-9538-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Caregiving Cause Psychological Distress? The Case for Familial and Genetic Vulnerabilities in Female Twins

Abstract: Background Informal caregiving can be deleterious to mental health, but research results are inconsistent and may reflect an interaction between caregiving and vulnerability to stress. Methods We examined psychological distress among 1,228 female caregiving and non-caregiving twins. By examining monozygotic and dizygotic twin pairs discordant for caregiving, we assessed the extent to which distress is directly related to caregiving or confounded by common genes and environmental exposures. Results Caregivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 58 publications
0
23
0
1
Order By: Relevance
“…Our findings concur with an earlier USA study that showed that having a close family member, such as a spouse/elderly parent, with dementia or other serious disability can lead to stress or depressive symptoms regardless of whether or not the unaffected family member is providing care (Amirkhanyan and Wolf, 2003). Furthermore, even in these difficult circumstances, not everyone may be affected, and Vitaliano et al in a unique twin-study suggests that the relationship between caregiving and psychological distress may be determined by a vulnerability largely shaped by genetic and early life factors (Vitaliano et al, 2014). Results from the multi-level models in our study purport that 33% of the variation in mental health is due to household factors, which would explain why household stressors such as living with someone with dementia symptoms could have the same influence on both caregiving and non-caregiving household members.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings concur with an earlier USA study that showed that having a close family member, such as a spouse/elderly parent, with dementia or other serious disability can lead to stress or depressive symptoms regardless of whether or not the unaffected family member is providing care (Amirkhanyan and Wolf, 2003). Furthermore, even in these difficult circumstances, not everyone may be affected, and Vitaliano et al in a unique twin-study suggests that the relationship between caregiving and psychological distress may be determined by a vulnerability largely shaped by genetic and early life factors (Vitaliano et al, 2014). Results from the multi-level models in our study purport that 33% of the variation in mental health is due to household factors, which would explain why household stressors such as living with someone with dementia symptoms could have the same influence on both caregiving and non-caregiving household members.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, characteristics associated with pre-implantation levels of strain may have particular value in identifying those at risk for prolonged exposure to elevated strain and its associated impact on morbidity and mortality. [9][10][11] Influence of HF Symptoms HF symptoms predicted both patient QOL and caregiver strain, demonstrating that the symptom experience (a hallmark of the HF syndrome) affects patients and caregivers alike. In patients, we observed that greater physical symptom burden was associated with worse pre-implantation QOL, a finding consistent with the existing literature.…”
Section: Change In Patient Qol and Caregiver Strainmentioning
confidence: 99%
“…8 Similarly, there is a call for more research on LVAD therapy caregivers, about whom little is known quantitatively but who likely experience considerable caregiver strain (often called "caregiver burden"), a subjective measure of stress related to caregiving that is a known predictor of increased morbidity and mortality. [8][9][10][11] More important, caregiver characteristics are known to influence patient outcomes and vice versa, in chronic illness in general and HF in particular, 12,13 supporting quantitative approaches in LVAD therapy that consider both patient and caregiver factors as predictors of patient and caregiver outcomes. Thus, the purpose of this analysis is to identify patient and caregiver determinants of patient QOL and caregiver strain in response to LVAD therapy.…”
mentioning
confidence: 99%
“…Así, cuidadores que han tenido problemas de salud mental de forma previa al cuidado tienen mayor probabilidad de recaer (Russo, Vitalino, Brewer, Katon y Becker, 1995), y el estado mental de los cuidadores en fases previas del proceso también predice el desarrollo de problemas posteriores (Joling et al, 2015). Factores genéticos, de personalidad o ambientales previos al cuidado contribuyen a predecir la ocurrencia de problemas psicológicos en el proceso de cuidado (Hooker, Monahan, Bowman, Frazier y Shifren, 1998;Vitaliano, Strachan, Dansie, Goldberg, y Buchwald, 2014). Entre estos factores se encuentran las habilidades sociales.…”
Section: Déficit En Habilidades Asertivasunclassified